Assessment of a self-deferral form for screening blood donors, Chiang Mai University Hospital, Thailand - Thaikruea L. (2014)
A self-deferral form has been used to screen Chiang Mai University Hospital blood donors and was improved in 2005. It has never been evaluated. The study aimed to assess the self-deferral form procedures in detecting infected donors. Sera from 5,083 donors, who passed the self-deferral screening form, were tested with the routine immuno-assays (serology) for HIV 1 and 2 antibodies, P24 antigen, HCV antibodies, HBV surface antigen, and syphilis. Antibody negative sera were also tested individually with the the Procleix Ultrio Assay for HIV-1 DNA, HCV RNA, and HBV DNA. The donors who had discrepant results between serology and NAT were evaluated with additional tests, including a more sensitive Alternative Nucleic Acid Test, AntiBcore IgM, AntiBcore IgG, HBsAg and Anti HBs. Among 5,083 donors, 331 (6.5%) had at least one positive marker. In multiple logistic regression analysis, the statistically significant factors (adjusted odds ratio and 95% Cl) for infection were age 30 years or below [1.45 (1.03, 2.03)], male gender [2.73 (1.64, 4.56)], primary school or lower education [1.56 (1.09, 2.23)], first-time donation [1.82 (1.25, 2.67)], and frequent donation [0.80 (0.70, 0.92)]. The safest donors were females, older than 30 years, with an education more than primary school, and frequent donation. Because of missing responses to some sensitive questions, there remains a need for further improvement of the self-deferral form.